First line chemotherapy plus trastuzumab in metastatic breast cancer HER2 positive - Observational institutional study - Meryem Aitelhaj; Siham Lkhoyaali; Ghizlane Rais; Saber Boutayeb; Hassan Errihani (The Pan African Medical Journal, 2016)

(untitled)
Breast cancer is the most common malignant disease and among the most frequent causes of cancer mortality in females worldwide. Metastatic breast cancer (MBC) is conventionally considered to be incurable. In first-line treatment of HER-2 positive MBC, randomized trials have demonstrated that trastuzumab when combined with chemotherapy significantly improves progression free survival and overall survival. To evaluate survival and toxicity of chemotherapy with Trastuzumab as first line therapy of human epithermal growth factor receptor 2 positive metastatic breast cancer, in Moroccan population. It is a phase IV observational institutional monocentric study. Including patients with metastatic breast cancer HER2 positive, as first-line chemotherapy combined with Trastuzumab from March 2009 until March 2010. Primary end point: progression free survival, secondary end point response rate and overall survival. A total of 20 patients were enrolled between March 2009 and March 2010. The lung was the first metastatic site in 60% of the cases, followed by bone, liver, nodes, skin and brain. All patients received chemotherapy with Trastuzumab: 9 of them with Docetaxel, 8 with vinorelbine, and 3 with capecitabine. The progression free survival was estimated by the Kaplan-Meier method, from the date of first cycle to the date of progression or at the last consultation, and the median was 12.8 months. Trastuzumab based chemotherapy was generally well tolerated; 5 patients (25%) presented cardiotoxicity. The results of this study join the literature and show the benefit of Trastuzumab to chemotherapy in first line metastatic breast cancer HER-2 positive.